2020
DOI: 10.1111/dgd.12701
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the core promoter factors TATA box binding protein and TATA box binding protein‐related factor 2 in Drosophila germ cells and their distinct functions in germline development

Abstract: In Drosophila, the expression of germline genes is initiated in primordial germ cells (PGCs) and is known to be associated with germline establishment. However, the transcriptional regulation of germline genes remains elusive. Previously, we found that the BTB/POZ-Zn-finger protein, Mamo, is necessary for the expression of the germline gene, vasa, in PGCs. Moreover, truncated Mamo lacking the BTB/POZ domain (MamoAF) is a potent vasa activator. In this study, we investigated the genetic interaction between Mamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Similar to TBP, TRF2 binds to promoters of all active genes. Previous studies in various species have shown that TBP and its paralogs occupy and regulate distinct sets of genes (82)(83)(84)(85)(86). It was therefore surprising that in mESCs, TRF2 binds to all active genes, though the differences may reflect species-specificity.…”
Section: The Tbp Paralog Trf2 Is Expressed In Mescs and Binds To Prommentioning
confidence: 99%
“…Similar to TBP, TRF2 binds to promoters of all active genes. Previous studies in various species have shown that TBP and its paralogs occupy and regulate distinct sets of genes (82)(83)(84)(85)(86). It was therefore surprising that in mESCs, TRF2 binds to all active genes, though the differences may reflect species-specificity.…”
Section: The Tbp Paralog Trf2 Is Expressed In Mescs and Binds To Prommentioning
confidence: 99%
“…Though these results could be explained by a critical requirement for the Ada2b-and Gcn5 containing ADA or Chiffon complexes [26,27] and no dependency on the SAGA complex during oogenesis, they may also reflect that distinct gene sets, defined by promoter types, have a different genetic requirement for each module. During Drosophila spermatogenesis and oogenesis, both TBP and the structurally related protein TBP-related factor 2 (TRF2) play critical, yet different roles, suggesting that different TBP-binding and/ or containing complexes may be required for oogenesis [28][29][30][31][32][33][34][35][36][37][38][39]. Therefore, we hypothesized that the SAGA complex itself and specifically the TBP-binding core module is important for oogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The SAGA core module interacts with TBP. TBP and the structurally related protein TBP-related factor 2 (TRF2) play critical, yet different roles during spermatogenesis and oogenesis [19][20][21][22][23]. Thus, we hypothesized that the core module is important for oogenesis via the activation of a distinct gene set, in a way that depends on TBP.…”
Section: Introductionmentioning
confidence: 99%